Brgy. elektronika promoting local independent electronic music to college students in Quezon City - Muncada, Paolo Jamin L.; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
Independent electronic music in the Philippines, in its present state, finds itself in a period of uncertainties and possibilities. While there is currently a growing audience for it, the struggle in legitimizing it in local music culture remains true as rock-based & traditional band music continue to dominate the independent music scene, leaving limited space for diverse musical acts. Therefore, local independent electronic artists bear the two-fold struggle of operating independently while being an artist who makes music outside of expected musical standards. With this, the research study aimed to design an intervention as a response to the question: how might we increase listenership to local independent electronic music among college students in Quezon City?

To address this, the researcher proposed Brgy. Elektronika, a multiplatform promotional campaign for local independent electronic music through social media, print materials, and on-ground activations geared towards college students in Quezon City. Ultimately, the campaign aimed at leading college students to platforms where they can engage with local independent electronic music such as curated weekly playlists, artist feature posts, and a listening session and culminating gig proposal. Through campaign testing with 18 user testers, Brgy. Elektronika showed positive results in increasing the awareness, listening preference, and interest of participants towards independent electronic music in the Philippines.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 74-78
Keywords: Music, Electronic; Original Pinoy Music (OPM); Music, Alternative; Music culture